Yaşam Biçimi ve Sanat Yapıtlarının Reklama Yansıması - Yıldız, Öykü Ezgi (İstanbul Kültür Üniversitesi Yayınları, 2007)
Çalışmada, başta ürün ya da hizmetin kimi temel özelliklerini aktaran bir araç konumunda olan reklamın süreç içinde toplumsal ve akçasal sonucunda yaşam biçimleri, imgeler yaratan bir ekinsel olguya dönüşümü ele alınmıştır. Çalışmada, küreselleşmenin reklam iletilerinin içrekleri üzerindeki etkisi, reklam ekin ve sanat yapıtı arasındaki ilinti irdelenmiştir. bu bağlamda Levi's reklamlarında kullanılan Davut Yontusu göstergebilimsel bir çözümlemeyle incelenerek, günümüzde reklamların iletilerinde sanat yapıtlarından yararlanarak tüketiciler üzerinde uyandırılmak istenilen güzelduyusal etkiye vurgu yapılmıştır.

In this paper, the advertisement primarily indicating the main principles of a product or a service will be under target. With regard to such an understanding, the process of advertisement's transformation into a cultural fact creating lifestyles and images is evaluated. In addition to the effect of globalization upon the content of commercial messages, the tripartite relationship among advertisement-culture-art work is also considered in this work. Regarding these considerations, the David Sculpture used in Levi's advertisement shall be analyzed in line with a semiological perspective. Besides, the adoption of artificial objects throughout the contemporary comercial messages in order to awake the sensation of beauty from the side of the advertisement-receiver is underlined.
Keywords: Ekin; Yaşam Biçimi; Sanat; Imge; Crop; Lifestyle; Art; Image